Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the expression for [tex]\((h \circ g)(-8)\)[/tex], we need to first understand that [tex]\((h \circ g)(x)\)[/tex] means [tex]\(h(g(x))\)[/tex]. Essentially, we are applying the function [tex]\(g(x)\)[/tex] first to the value [tex]\(-8\)[/tex], and then taking the result and applying the function [tex]\(h(x)\)[/tex] to it. Here are the step-by-step details:
1. Step 1: Calculate [tex]\(g(-8)\)[/tex]
The function [tex]\(g(x)\)[/tex] is defined as:
[tex]\[ g(x) = 4x - 2 \][/tex]
Substitute [tex]\(x = -8\)[/tex] into the function [tex]\(g(x)\)[/tex]:
[tex]\[ g(-8) = 4(-8) - 2 = -32 - 2 = -34 \][/tex]
Thus, [tex]\(g(-8) = -34\)[/tex].
2. Step 2: Calculate [tex]\(h(-34)\)[/tex]
Now that we have [tex]\(g(-8) = -34\)[/tex], we need to use this result as the input for the function [tex]\(h(x)\)[/tex]. The function [tex]\(h(x)\)[/tex] is defined as:
[tex]\[ h(x) = \frac{1}{2}x + 6 \][/tex]
Substitute [tex]\(x = -34\)[/tex] into the function [tex]\(h(x)\)[/tex]:
[tex]\[ h(-34) = \frac{1}{2}(-34) + 6 = -17 + 6 = -11 \][/tex]
Therefore, [tex]\(h(-34) = -11\)[/tex].
So, to summarize, the calculation is as follows:
1. [tex]\(g(-8) = -34\)[/tex]
2. [tex]\(h(-34) = -11\)[/tex]
Thus, the expression for [tex]\((h \circ g)(-8)\)[/tex] is:
[tex]\[ (h \circ g)(-8) = -11 \][/tex]
1. Step 1: Calculate [tex]\(g(-8)\)[/tex]
The function [tex]\(g(x)\)[/tex] is defined as:
[tex]\[ g(x) = 4x - 2 \][/tex]
Substitute [tex]\(x = -8\)[/tex] into the function [tex]\(g(x)\)[/tex]:
[tex]\[ g(-8) = 4(-8) - 2 = -32 - 2 = -34 \][/tex]
Thus, [tex]\(g(-8) = -34\)[/tex].
2. Step 2: Calculate [tex]\(h(-34)\)[/tex]
Now that we have [tex]\(g(-8) = -34\)[/tex], we need to use this result as the input for the function [tex]\(h(x)\)[/tex]. The function [tex]\(h(x)\)[/tex] is defined as:
[tex]\[ h(x) = \frac{1}{2}x + 6 \][/tex]
Substitute [tex]\(x = -34\)[/tex] into the function [tex]\(h(x)\)[/tex]:
[tex]\[ h(-34) = \frac{1}{2}(-34) + 6 = -17 + 6 = -11 \][/tex]
Therefore, [tex]\(h(-34) = -11\)[/tex].
So, to summarize, the calculation is as follows:
1. [tex]\(g(-8) = -34\)[/tex]
2. [tex]\(h(-34) = -11\)[/tex]
Thus, the expression for [tex]\((h \circ g)(-8)\)[/tex] is:
[tex]\[ (h \circ g)(-8) = -11 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.